Hail, Caesar! [videorecording (DVD)] - Coen, Joel; Coen, Ethan; Brolin, Josh; Clooney, George; Fiennes, Ralph; Johansson, Scarlett, 1984-; Swinton, Tilda; McDormand, Frances; Tatum, Channing; Hill, Jonah, 1983- (Universal Pictures Home Entertainment, 2016)
An all-star comedy set during the latter years of Hollywood's Golden Age. It follows a single day in the life of a studio fixer who is presented with plenty of problems to fix.